2018
DOI: 10.1021/acsomega.8b03155
|View full text |Cite
|
Sign up to set email alerts
|

pH-Triggered Membrane in Pervaporation Process

Abstract: Dehydration of binary methyl acetate–water mixtures under neutral, acidic, and basic conditions was carried out by using PERVAP composite membranes based on polyvinyl alcohol and poly(1-vinylpyrrolidone- co -2-(dimethylamino)ethyl methacrylate) P(VP- co -DMAEMA). The effects of an acid (HCl) and a base (NaOH) on the separation performance of the membrane during the pervaporation process were investigated. The pH-responsive nature of membranes has been confirmed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The shift of these maxima to lower wavenumbers suggests that the N–H and C=O groups of PDMAEMA and MBA are involved in the hydrogen bond formation. The results of the FTIR analysis are in agreement with the literature data [ 40 , 41 , 42 , 43 , 44 ].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The shift of these maxima to lower wavenumbers suggests that the N–H and C=O groups of PDMAEMA and MBA are involved in the hydrogen bond formation. The results of the FTIR analysis are in agreement with the literature data [ 40 , 41 , 42 , 43 , 44 ].…”
Section: Resultssupporting
confidence: 90%
“…Almost equal swelling of 1-3 samples in alkaline and acidic medium studied over a longer period makes likely its use for specific applications such as medicine, pharmaceuticals for drug delivery, sensor manufacturing, separators in electrochemical devices (batteries, capacitors and the like), etc. [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…14 In a previous work, we have investigated some of those membranes as pH-responsive, and we have demonstrated that they can be also applied in solvent dehydration processes by varying the pH of the mixture. 15 However, due to the low degree of cross-linking and presence of the copolymer, those membranes show poor performance for ethanol/ water separation, that is, the selectivity is too low. Thus, being encouraged by the results of our previous study, we hypothesized that the synthesis and use of tailor-made copolymers (rather than commercial copolymers produced for other applications) based on N-vinylpyrrolidone (NVP), 2-(dimethylamino)ethyl methacrylate (DMAEMA) and Nvinylimidazole (NVIm) with a controlled molar ratio of monomers in the copolymer, can improve the water/ ethanol selectivity of this type of membranes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 34 ] The peak at 1400 cm −1 is the absorption peak of the C–N stretching vibrations of PVP. [ 35 ] The bands located at 2900 and 2980 cm −1 are related to the CH 2 asymmetric stretching mode of PVP and PEO. [ 36,37 ] The peak located at 3670 cm −1 is from quartz glass.…”
Section: Resultsmentioning
confidence: 99%